2019
DOI: 10.1136/annrheumdis-2018-214539
|View full text |Cite
|
Sign up to set email alerts
|

Synovial cellular and molecular signatures stratify clinical response to csDMARD therapy and predict radiographic progression in early rheumatoid arthritis patients

Abstract: ObjectivesTo unravel the hierarchy of cellular/molecular pathways in the disease tissue of early, treatment-naïve rheumatoid arthritis (RA) patients and determine their relationship with clinical phenotypes and treatment response/outcomes longitudinally.Methods144 consecutive treatment-naïve early RA patients (<12 months symptoms duration) underwent ultrasound-guided synovial biopsy before and 6 months after disease-modifying antirheumatic drug (DMARD) initiation. Synovial biopsies were analysed for cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
250
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 250 publications
(276 citation statements)
references
References 29 publications
20
250
2
4
Order By: Relevance
“…Overall, these data provide insights into the specific associations of immune cells with clinical phenotypes and highlight the relevance of B cells as markers of ongoing synovitis associated with a clinical phenotype of aggressive disease in early RA. However, alternative histologic scoring systems that aim to more comprehensively assess immune cell infiltration are available, including an integrated histologic scoring system that we have recently developed and that has been verified by combined histologic and ‐omics approaches . Although it is likely that in the near future integrated histologic and molecular analyses will identify novel or previously unrecognized pathways mediating treatment response or resistance, in order to translate those studies to routine clinical care there is a need for well‐validated histopathologic scores that can be easily applied for patient classification, such as the B cell synovitis score described herein, particularly if it were demonstrated to have clinical utility for stratifying patients to receive rituximab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, these data provide insights into the specific associations of immune cells with clinical phenotypes and highlight the relevance of B cells as markers of ongoing synovitis associated with a clinical phenotype of aggressive disease in early RA. However, alternative histologic scoring systems that aim to more comprehensively assess immune cell infiltration are available, including an integrated histologic scoring system that we have recently developed and that has been verified by combined histologic and ‐omics approaches . Although it is likely that in the near future integrated histologic and molecular analyses will identify novel or previously unrecognized pathways mediating treatment response or resistance, in order to translate those studies to routine clinical care there is a need for well‐validated histopathologic scores that can be easily applied for patient classification, such as the B cell synovitis score described herein, particularly if it were demonstrated to have clinical utility for stratifying patients to receive rituximab.…”
Section: Discussionmentioning
confidence: 99%
“…However, the degree of synovial B cell infiltrate is a highly variable phenomenon, ranging from complete absence to a dense distribution within organized infiltrates in up to 40% of patients and as such has been examined as a potential source of predictive and prognostic biomarkers in RA. Indeed, recent data from a large cohort of patients with untreated early RA have suggested that a B cell–rich lymphoid synovitis is associated with highly active disease and predictive of radiographic progression . However, comparison of these data with other cohorts that either support or refute this notion is challenging due to a lack of consistency in quantitative and qualitative assessment of B cell synovitis, the effects of concomitant diverse therapy, and examination of patients at variable disease stages and levels of disease activity.…”
Section: Introductionmentioning
confidence: 99%
“…Patients were enrolled in the Pathobiology of Early Arthritis Cohort (PEAC, details at http://www.peac-mrc. mds.qmul.ac.uk/index.php) at the Centre for Experimental Medicine and Rheumatology at Queen Mary University of London (REC 05/Q0703/198, London, UK), as previously described (Kelly et al, 2015;Humby et al, 2019;Lewis et al, 2019). All patients belonging to this cohort underwent baseline ultrasound-guided biopsy on the most inflamed accessible joint.…”
Section: Experimental Model and Subject Detailsmentioning
confidence: 99%
“…Progressive disability and systemic complications are still a burden leading to socioeconomic costs and unmet needs. Indeed, current conventional and biologic disease modifying therapies produce good responses in only 60% of patients (Humby et al, 2019). Predictive biomarkers of prognosis, therapeutic response, and resistance to treatment, which currently include ACPA, RF, C-reactive protein (CRP), and erythrocyte sedimentation rate (ESR), remain inadequate from a clinical decision making perspective (McInnes and Schett, 2011;Dennis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%